Sustainable dye remediation using fruit-derived activated carbon - Alaa M Al-Ma’abreh; Dareen A Hmedat; Gada Edris; Fida’ F Odeh; Mariam A Hamed (Adsorption Science & Technology)
In this research, Casuarina equisetifolia fruit-based-activated carbon (CAC) was employed to investigate the simultaneous removal of crystal violet (CV), Naphthol Black Blue (NBB), and methyl orange (MO) in one mixture from aqueous solutions. The efficacy of adsorbent removal was studied concerning adsorption characteristics such as pH, dose of CAC, initial dye concentration, and adsorption time. Fourier transform infrared (FTIR), scanning electron microscope (SEM), and UV-visible analysis all showed that the dye mixture stuck to the CAC surface at the same time. Results revealed the best simultaneous adsorption efficiencies for the investigated dyes were attained in the pH range of 3–10, with a CAC dose of 0.08 g. The optimal initial concentration for the dye mixture was found to be 40 mg·L −1 . The optimal contact time for CV, NBB, and MO was 45 min. Kinetic studies revealed a pseudo-second-order adsorption mechanism for the dye mixture. The Freundlich isotherm model best described the equilibrium data. The maximum adsorption capacities were CV (239.23 mg·g −1 ), NBB (134.95 mg·g −1 ), and MO (45.93 mg·g −1 ). Thermodynamic analysis suggests these adsorption processes to be endothermic and spontaneous. The findings of high adsorption capacities highlight the practical applicability of this approach in addressing complex dye pollution challenges.